1981
DOI: 10.1152/jappl.1981.50.4.851
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of breathing and swallowing in human infants

Abstract: Spontaneous nonfeeding swallows taken during wakefulness and sleep were identified in nine preterm infants by characteristic patterns in pharyngeal pressure, submental electromyogram, and respiratory airflow. Two hundred and seventeen swallows during ongoing respiration interrupted either inspiratory or expiratory airflow with airway closure for approximately 1 s. The duration of airway closure was independent of respiratory rate. A brief "swallow-breath" was associated with swallow onset in most instances. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 0 publications
4
93
0
Order By: Relevance
“…A recent study on eight term and five preterm infants (2-7 wk postnatal) found that sucking during bottle feeds could occur in inspiration or expiration (1). In continuous sucking, there was a fairly During the first 15 s, swallows occur at end-inspiration ( 7 ) , mid-expiration ( 9 ) , and end-inspiration followed by a pause (4). The onset of regular breathing (u) corresponds to the start of a period of stable coordination between swallows and breaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on eight term and five preterm infants (2-7 wk postnatal) found that sucking during bottle feeds could occur in inspiration or expiration (1). In continuous sucking, there was a fairly During the first 15 s, swallows occur at end-inspiration ( 7 ) , mid-expiration ( 9 ) , and end-inspiration followed by a pause (4). The onset of regular breathing (u) corresponds to the start of a period of stable coordination between swallows and breaths.…”
Section: Discussionmentioning
confidence: 99%
“…The swallow recording methods were based on those of Wilson et a/. (9) and Pierantoni et al (10). Respiratory recording used standard polysomnography techniques.…”
Section: Methodsmentioning
confidence: 99%
“…55,56 They often respond to fluid in the oropharynx with prolonged apnea, an exaggerated protective response. 57,58 The size of the fluid bolus, the speed with which it travels through the oropharynx, the number of swallows needed to clear the bolus, and the postconceptional age of the infant all affect changes in the respiratory pattern to accommodate swallowing.…”
Section: Ability To Coordinate Swallowing and Breathingmentioning
confidence: 99%
“…19,38,59 Preterm infants often suck in excess of their capacity to swallow, which places a large bolus of fluid in the mouth, requiring several swallows to clear and obstructing the airway for a prolonged period. 55,56 Hanlon and colleagues found that apnea time during swallowing and the incidence of multiple swallows decreased as healthy preterm infants matured. Preterm infants continued to have longer swallowing apneic events at term than full-term infants do, however.…”
Section: Ability To Coordinate Swallowing and Breathingmentioning
confidence: 99%
“…This reflexively induced inspiratory activity has been observed in felines (Gestreau, Milano, Bianchi, & Grelot, 1996;Hukuhara & Okada, 1956) and humans (Hardemark Cedborg et al, 2009;Wilson, Thach, Brouillette, & Abu-Osba, 1981). Schluckatmung activity can be distinguished from gradual onset and offset of the eupneic rhythmic breathing, which is 9 normal breathing pattern.…”
Section: Thoracic Diaphragmmentioning
confidence: 72%